2013
DOI: 10.5755/j01.ee.23.5.1979
|View full text |Cite
|
Sign up to set email alerts
|

The impact of capital structure on the performance efficiency of Baltic listed companies

Abstract: The capital structure can influence the behavior of the company as well as its performance results and its value. However, the effect can be quite different. The financial indicators of Lithuanian, Latvian and Estonian listed companies published in their annual reports have been used in order to investigate the impact of capital structure on performance efficiency of the companies. The research included data of only non-financial companies, because the capital structure of financial institutions is specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
0
17
0
6
Order By: Relevance
“…(2014) teigia, jog įmonės finansinės veiklos efektyvumą objektyviausiai parodo kapitalo pelningumo rodikliai. Šiuo pelningumu labiausiai domisi kapitalo savininkai, kreditoriai ir investuotojai, nes iš šių rodiklių galima spręsti apie investicijų pelningumą ir galimybę gauti dividendų (Norvaišienė, 2012). Nuosavo kapitalo pelningumas parodo nuosavo kapitalo sukurtą pelną ir tam tikru aspektu -įmonės vadovybės darbo efektyvumą naudojant investuotą kapitalą (Hutabarat ir Simanjuntak, 2013).…”
Section: Tyrimo Metodikaunclassified
See 2 more Smart Citations
“…(2014) teigia, jog įmonės finansinės veiklos efektyvumą objektyviausiai parodo kapitalo pelningumo rodikliai. Šiuo pelningumu labiausiai domisi kapitalo savininkai, kreditoriai ir investuotojai, nes iš šių rodiklių galima spręsti apie investicijų pelningumą ir galimybę gauti dividendų (Norvaišienė, 2012). Nuosavo kapitalo pelningumas parodo nuosavo kapitalo sukurtą pelną ir tam tikru aspektu -įmonės vadovybės darbo efektyvumą naudojant investuotą kapitalą (Hutabarat ir Simanjuntak, 2013).…”
Section: Tyrimo Metodikaunclassified
“…Atlikta literatūros analizė parodė, jog Norvaišienė (2012), Žilinskij ir Rutkauskas (2012), Tamošiūnienė ir Paškevičienė (2016) nagrinėdami akcijų kainų sąsajas su įmonės finansiniais rodikliais skaičiuoja grynojo pelningumo, turto pelningumo ir nuosavo kapitalo pelningumo rodiklius, kurie geriausiai parodo įmonės veiklos galutinius rezultatus.…”
Section: Tyrimo Metodikaunclassified
See 1 more Smart Citation
“…The examination of these relationships has also led our study to explore the role that efficiency has on firms' capital structure in order to gain insight into the significance of relationships in particular related to cash flow. To date, this topic has received little attention by the research literature (Berger & Bonaccorsi di Patti, 2006;Margaritis & Psillaki, 2007;Norvaisiene, 2012). Berger and Bonaccorsi di Patti (2006) analyzed profit efficiency and capital structure for the US banking industry.…”
Section: Introductionmentioning
confidence: 99%
“…Using Data Envelopment Analysis, Margaritis and Psillaki (2007) found that the efficiency of 12,240 New Zealand firms has a positive effect on leverage at low to mid-leverage levels and a negative effect at high leverage ratios. Norvaisiene (2012) focused on the reverse causality from capital structure to efficiency.…”
Section: Introductionmentioning
confidence: 99%